Implications of sheep and cattle Teline linifolia bush ingestion behaviour for managing the Maamora cork tree forest (Morocco) (CAHIERS AGRICULTURES, 2009)
The cork tree forest of Maamora near Rabat (Maroc) has suffered deep and increasing grazing pressure for 100 years. Dense understorey stands of Teline linifolia, a native, nitrogen fixing and vigorous legume shrub, would contribute to forest regeneration provided that it be proven to be a resource for sheep and cattle grazing. Autumn is a period with lower resources of grass and with no nitrogen fixing shrubs. In situ monthly measurements of sheep and cattle ingestion rates show a significant contribution of T. linifolia in both sheep (up to 24%) and cattle (up to 12%) total ingestion rates in autumn, due to its peculiar phenology along with the inadequacy of grass and other shrub resources at this time. The opportunity of planting Teline shrubs in the process of cork tree forest regeneration along with multi-purpose uses is described and discussed.